The Application of the Health Belief Model in the Selection of Acupuncture Therapy for Low Back Pain Patients - Ningrum, Anis Lupita; Prasetya, Hanung; Murti, Bhisma; Demartoto, Argyo (Indonesian Journal of Medicine, 2025)
Background: Low back pain (LBP) is one of the health problems experienced by 50–80% of adults. LBP affects individual, physical, social, and psychological aspects. Individuals suffering from LBP require comprehensive treatment to ensure the success of therapy. The study aims to determine the patient's perception of the choice of LBP therapy using the Health Belief Model theory. Subjects and Method: This research was conducted using a cross-sectional study conducted in Surakarta, from September to October 2024. A total of 200 acupuncture patients and physiotherapy patients were selected using fixed disease sampling. The independent variables were vulnerability perception, severity perception, benefit perception, obstacle perception, cues to action perception, self-efficacy. The bound variable is the choice of therapy. The data using questionnaires were analyzed using multiple logistic regression. Results: Perceived susceptibility was less likely to use acupuncture therapy (OR= 0.51; 95% CI= 0.14 to 1.79; p=0.293). Perceived severity was more likely to use acupuncture therapy (OR=3.99; 95% CI= 1.17 to 13.54; p= 0.027). Perceived benefits were more likely to use acupuncture therapy (OR=43.90; 95% CI= 9.45 to 203.99; p<0.001). Perceived barriers were less likely to use acupuncture therapy (OR=0.03; 95% CI p< 0.01 to 0.20; p< 0.001). Cues to action were more likely to use acupuncture therapy (OR=7.10; 95% CI p= 2.20 to 22.91; p< 0.001). High self-efficacy has a greater likelihood of using acupuncture therapy (OR=142.49; 95% CI= 14.17 to 1432.86; p<0.001). Conclusion: The Health Belief Model for the selection of acupuncture therapy increased with the perception of severity, perception of benefits, action signals, and self-efficacy. The choice of acupuncture therapy decreased with a high perception of resistance. Perception of vulnerability was statistically not significantly associated with therapy selection. The independent variables in the model were able to explain the variation in therapy selection (acupuncture vs physiotherapy) by 68.69%.